The Challenges Faced By Dental Students in Studying Oral Pathology Online During Covid-19: A Cross-Sectional Study - Seeme Nigar; Hira khanzada; Afsheen Maqsood; Maria Ghani; Ahmed Bin Khalid; Sabeen Masood (Gandhara University, 2023)
OBJECTIVES The way of practising and teaching dentistry has changed significantly worldwide due to the COVID-19 pandemic, and the impact on dental education should not be neglected. Therefore, sharing experiences about online teaching from in-person education is essential to a better learning process during this period. This study aimed to assess the challenges faced by dental students in studying oral pathology online during covid-19: a cross-sectional study. METHODOLOGY It was a descriptive cross-sectional study in the Department of oral pathology at Altamash Institute of dental medicine to assess the challenges students faced during the COVID-19 pandemic. A total of 110 participants were approached, and among them, 105 participants responded. Of 105 participants, 78% were females, and 22% were males. Data were analyzed using SPSS version 23. RESULTS Almost 93.3% of the students felt in-person lectures are more effective than online lectures. Fourth-year students showed higher satisfaction with the number of online tutorial / practical classes taken to provide an in-depth view of the subject than 3rd year students (8.8% vs 91.2%, p=0.045). Fourth-year students showed significantly higher satisfaction with several online theory classes to provide an in-depth view of the subject than 3rd year students (p=0.045). CONCLUSION The present study concluded that most students prefer in person classes over virtual learning and face a lack of online interaction with the faculty.